FIDIC red book : a companion to the 2017 construction contract - Srensen, Jakob B. (ICE Publishing, 2019)
FIDIC Red Book is a practical guide for anyone involved in preparing, administering, or contributing to the FIDIC suite of contracts, 2017 edition. Designed as a companion for both the first-time and also more experienced user, the book presents an accessible guide to the 21 clauses of the 2017 FIDIC Conditions of Contract, using the Conditions of Contract for Construction (Red Book) as a basis. Opening chapters provide an introduction to international construction contracts, including the entire FIDIC suite of contracts, and there is also a list of definitions of key terms. Chapters in Part 2 provide a brief introduction to each of the Clauses and Sub-Clauses in the Red Book, and explain how they are interlinked. A final section provides a concise practical guide to the use of the FIDIC Conditions, and a summary of special provisions discussed in Part 2.
Keywords: International Federation of Consulting Engineers. -- Construction contract 2017.; Construction contracts -- Handbooks, manuals, etc.; elektronické knihy; electronic books